Libyan-Soviet economic relations during the Republican era 1969-1977 AD (Journal of Human Sciences, 2025)
The Soviet Union emerged as a global power with influence on the international scene after World War II (1939-1945). After Stalin's death, it began to look to strengthen its relations with the Middle Eastern countries, including Libya. Libya, which gained independence in late 1951, has had strong political and economic relations with the West, especially Britain and the United States, since its independence.Diplomatic relations between the two countries were established in 1955. However, these relations between the two parties did not witness political or economic development throughout the royal era in Libya.